Perioperative cardiac arrest: a study of 53718 anaesthetics over 9 yr from a Brazilian teaching hospital - Braz, Leandro Gobbo [UNESP]; Modolo, NSP; do Nascimento, P.; Bruschi, BAM; Castiglia, YMM; Ganem, Eliana Marisa [UNESP]; de Carvalho, L. R.; Braz, José Reinaldo Cerqueira [UNESP] (Oxford University Press, 2006)
Background. Little information exists regarding factors influencing perioperative cardiac arrests and their outcome. This survey evaluated the incidence, causes and outcome of perioperative cardiac arrests in a Brazilian tertiary general teaching hospital between April 1996 and March 2005.Methods. The incidence of cardiac arrest during anaesthesia was prospectively identified from an anaesthesia database. There were 53 718 anaesthetics during the study period. Data collected included patient characteristics, surgical procedures (elective, urgent or emergency), ASA physical status classification, anaesthesia provider information, type of surgery, surgical areas and outcome. All cardiac arrests were retrospectively reviewed and grouped by cause of arrest and death into one of four groups: totally anaesthesia related, partially anaesthesia related, totally surgery related or totally patient disease or condition related.Results. One hundred and eighty-six cardiac arrests (34.6:10 000) and 118 deaths (21.97:10 000) were found. Major risk factors for cardiac arrest were neonates, children under 1 yr and the elderly (P < 0.05), male patients with ASA III or poorer physical status (P < 0.05), in emergency surgery (P < 0.05) and under general anaesthesia (P < 0.05). Patient disease/condition was the major cause of cardiac arrest or death (P < 0.05). There were 18 anaesthesia-related cardiac arrests (3.35:10 000)-10 totally attributed (1.86:10 000) and 8 partially related to anaesthesia (1.49:10 000). There were 6 anaesthesia-related deaths (1.12:10 000)-3 totally attributable and 3 partially related to anaesthesia (0.56:10 000 in both cases). The main causes of anaesthesia-related cardiac arrest were respiratory events (55.5%) and medication-related events (44.5%).Conclusions. Perioperative cardiac arrests were relatively higher in neonates, infants, the elderly and in males with severe underlying disease and under emergency surgery. All anaesthesia-related cardiac arrests were related to airway management and medication administration which is important for prevention strategies.
Keywords: anaesthesia; complications, cardiac arrest; outcomes